Classification of nutritional status by age groups and development of obesity in young people with down syndrome of the fundación luisa fernanda simdrome down of Medellín, Colombia (2020)
Dear colleagues and participants, Welcome to this special supplement dedicated to compiling the abstracts of the communications and lectures of the FINUT 2020 Conference. The supplement accounts for 339 abstracts for oral and poster communications from 18 countries. It also comprises the abstracts of more than 80 selected guest speakers participating in the scientific symposia and special lectures. The main objective of the FINUT Conference, which will be held every two years, is to create a space for exchange and discussion of ideas regarding the main challenges of Food and Nutrition in Iberoamerica, to provide solutions aimed at improving the health of the populations of the region, where all the stakeholders, both public and private, are present and can share their thoughts. In addition, the Conference seeks to open a place for contrasted science shared by the Iberoamerican region, a necessary space to open opportunities and to display the research work done in Food and Nutrition, especially that from Latin American countries. The scientific program of the Conference includes 32 parallel symposia, 4 meetings with the experts and 10 special lectures. In this first edition the Conference focused on 4 topics: • Challenges of nutrition and public health in Iberoamerica. • Nutrition in the prevention and treatment of chronic diseases. • Safe, healthy, and sustainable foods. • Challenges for an effective and efficient public-private partnership in food and nutrition. The Conference is organized by the Iberoamerican Nutrition Foundation (FINUT), a nonprofit organization founded in 2011 by the International Union of Nutritional Sciences (IUNS), the Latin American Society of Nutrition (SLAN), and the Spanish Nutrition Society (SEÑ) to promote knowledge, research, development and innovation of Nutrition and Food in Iberoamerica. The FINUT programs are aimed at training professionals and researchers interested in these areas and building partnerships with governments, universities, research centers and other organizations. Although we are living moments full of uncertainty, the FINUT 2020 virtual Conference organizers would like to thank all our speakers, attendees, and collaborators for their effort to share the scientific advances in the fields of nutrition and food sciences. The organization acknowledges and congratulates all the FINUT 2020 participants and members of the committees for their ability to adapt to new communication needs and hope that in the next edition of the Conference we can give you all the very personal thanks for moving forward Ann Nutr Metab 2020;76(suppl 4):1–232 Published online: October 9, 2020 Downloaded from http://karger.com/anm/article-pdf/76/Suppl. 4/1/4020422/000511826.pdf by guest on 01 July 2024 and for continuing the valuable work of providing the world with true and scientifically verified research, so essential in these times. ¡We are looking forward to seeing you at the FINUT 2022 Conference!